2021
DOI: 10.1037/rev0000258
|View full text |Cite
|
Sign up to set email alerts
|

The Leaky Integrating Threshold and its impact on evidence accumulation models of choice response time (RT).

Abstract: A common assumption in choice response time modelling is that after evidence accumulation reaches a certain decision threshold, the choice is categorically communicated to the motor system that then executes the response. However, neurophysiological findings suggest that motor preparation partly overlaps with evidence accumulation, and is not independent from stimulus difficulty level. We propose to model this entanglement by changing the nature of the decision criterion from a simple threshold to an actual pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 70 publications
(141 reference statements)
3
43
0
Order By: Relevance
“…For this analysis, Speed and Accuracy data are fitted completely independently, resulting in different parameters for each instruction. In line with Verdonck et al 27 , we found that both leak ( p < 10 −17 ) and boundary separation ( p < 10 −8 ) were significantly different between Speed and Accuracy conditions, while relative starting position zr ( p = 0.32) and drift speeds v i =1…4 ( p = 0.55, p = 0.08, p = 0.29, p = 0.20) were indistinguishable.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…For this analysis, Speed and Accuracy data are fitted completely independently, resulting in different parameters for each instruction. In line with Verdonck et al 27 , we found that both leak ( p < 10 −17 ) and boundary separation ( p < 10 −8 ) were significantly different between Speed and Accuracy conditions, while relative starting position zr ( p = 0.32) and drift speeds v i =1…4 ( p = 0.55, p = 0.08, p = 0.29, p = 0.20) were indistinguishable.…”
Section: Resultssupporting
confidence: 91%
“…For this analysis, Speed and Accuracy data are fitted completely independently, resulting in different parameter values for each instruction. In line with Verdonck et al (2021), we found that inverse leak λ −1 and boundary separation a were significantly smaller in the Speed than in the Accuracy condition looking at their intra-individual differences (∆λ −1 = −0.19 [−0.22, −0.15], ∆a = −0.089 [−0.12, −0.061]). In addition, the relative starting position zr and drift speeds v i=1..…”
Section: Leak Vs Boundary Adjustments For Controlling Choice Urgencysupporting
confidence: 82%
See 2 more Smart Citations
“…It simply assumes a gate (EMG threshold) at the M1 level above which accumulated evidence is transmitted to the muscle. Verdonck et al (2020) recently proposed a leaky integrated threshold architecture (LIT) that models the flow of information from perceptual evidence accumulation to the motor structures that prepare the response, such as M1. Specifically, LIT models perceptual evidence accumulation with a standard DDM, and assumes that motor preparation builds upon a leaky accumulation process that takes the accumulated evidence of the perceptual process as a continuous input.…”
Section: Discussionmentioning
confidence: 99%